Fas Signaling in Dendritic Cells Mediates Th2 Polarization in HDM-Induced Allergic Pulmonary Inflammation - Han, Miaomiao; Hu, Ran; Ma, Jingyu; Zhang, Baohua; Chen, Ce; Li, Huabin; Yang, Jun; Huang, Gonghua (Frontiers in Immunology, 2018)
Fas–Fas ligand (FasL) signaling plays an important role in the development of allergic inflammation, but the cellular and molecular mechanisms are still not well known. By using the bone marrow-derived dendritic cell (BMDC) transfer-induced pulmonary inflammation model, we found that house dust mite (HDM)-stimulated FAS-deficient BMDCs induced higher Th2-mediated allergic inflammation, associated with increased mucus production and eosinophilic inflammation. Moreover, FAS-deficient BMDCs promoted Th2 cell differentiation upon HDM stimulation in vitro. Compared to wild-type BMDCs, the Fas-deficient BMDCs had increased ERK activity and decreased IL-12 production upon HDM stimulation. Inhibition of ERK activity could largely increase IL-12 production, consequently restored the increased Th2 cytokine expression of OT-II CD4+ T cells activated by Fas-deficient BMDCs. Thus, our results uncover an important role of DC-specific Fas signaling in Th2 differentiation and allergic inflammation, and modulation of Fas signaling in DCs may offer a useful strategy for the treatment of allergic inflammatory diseases.